Composite particle, positive electrode, all-solid-state battery, and method for producing composite particle
Patent Information
- Application Number
- JP2022053182
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-29
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2042-03-29
AI Technical Summary
【0007】 以下、本開示の技術的構成および作用効果が説明される。ただし本明細書の作用メカニズムは推定を含む。作用メカニズムは本開示の技術的範囲を限定しない。
Smart Images

Figure 0007652121000002 
Figure 0007652121000003 
Figure 0007652121000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite particle, a positive electrode, an all-solid-state battery, and a method for producing the composite particle. [Background technology]
[0002] Japanese Patent Laid-Open Publication No. 2010-135090 (Patent Document 1) discloses forming a reaction suppressing portion on the surface of a positive electrode active material by a PLD (Pulsed Laser Deposition) method. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-135090 A Summary of the Invention [Problem to be solved by the invention]
[0004] Sulfide-based all-solid-state batteries (hereinafter may be abbreviated as "all-solid-state batteries") have been developed. All-solid-state batteries contain a sulfide solid electrolyte. If the sulfide solid electrolyte comes into direct contact with the positive electrode active material particles, the sulfide solid electrolyte may deteriorate. The deterioration of the sulfide solid electrolyte (ion conduction path) may increase the battery resistance. Therefore, it has been proposed to form a coating film on the surface of the positive electrode active material particles. The coating film prevents direct contact between the positive electrode active material particles and the sulfide solid electrolyte, which may reduce the deterioration of the sulfide solid electrolyte. This is expected to reduce the initial resistance.
[0005] Conventionally, it has been proposed to form a coating film by a gas phase method (e.g., PLD method, etc.). Instead of the gas phase method, it is also possible to form a coating film by a liquid phase method. That is, it is possible to form a coating film by drying a coating liquid on the surface of the positive electrode active material particles. By adopting the liquid phase method, for example, improvement of mass productivity is expected. However, the liquid phase method tends to have a small effect of reducing the initial resistance.
[0006] An object of the present disclosure is to reduce the initial resistance. [Means for solving the problem]
[0007] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0008] 1. The composite particle includes a positive electrode active material particle and a coating film. The coating film covers at least a part of the surface of the positive electrode active material particle. The coating film includes a first layer and a second layer. The first layer includes a phosphorus compound. The second layer includes a boron compound.
[0009] Conventionally, coating films have a single-layer structure. In contrast, the coating film described in "1." above has a specific multilayer structure. That is, the coating film includes a first layer and a second layer. The first layer includes a phosphorus compound, and the second layer includes a boron compound. Although the details of the mechanism are unknown, it is expected that the coating film including the first and second layers will reduce the initial resistance.
[0010] 2. In the composite particle according to the above item "1," the coating film may include, for example, a first laminated portion. In the first laminated portion, the first layer is interposed between the positive electrode active material particles and the second layer.
[0011] In the coating film described in "1." above, the first layer and the second layer may be stacked in any order. For example, the first layer may be stacked first, followed by the second layer, in a portion where the first layer and the second layer are stacked.
[0012] 3. In the composite particle described in "1." above, the coating film may include, for example, a second laminated portion. In the second laminated portion, the second layer is interposed between the positive electrode active material particles and the first layer.
[0013] For example, there may be a portion where the second layer and the first layer are laminated in that order.
[0014] 4. The composite particle according to any one of the above items "1." to "3." may have a coverage of, for example, 95% or more. The coverage is measured by X-ray photoelectron spectroscopy (XPS).
[0015] The coating film having a multi-layer structure is expected to improve the coverage, for example. The improved coverage is expected to reduce the initial resistance, for example.
[0016] 5. The positive electrode includes the composite particles according to any one of the above items "1." to "4." and a sulfide solid electrolyte.
[0017] 6. The all-solid-state battery comprises the positive electrode described in "5." above.
[0018] 7. A method for producing a composite particle includes the following (a) and (b): (a) Positive electrode active material particles are prepared. (b) Composite particles are produced by forming a coating film on the surfaces of positive electrode active material particles. The above (b) includes the following (b1) and (b2). (b1) The first coating liquid is dried to form a first layer. (b2) The second coating liquid is dried to form a second layer. The first layer includes a phosphorus compound, and the second layer includes a boron compound.
[0019] According to the manufacturing method described in "7." above, the composite particles described in "1." above can be manufactured.
[0020] 8. In the method for producing a composite particle described in "7." above, the coating film may be formed to include a first laminated portion. In the first laminated portion, the first layer is interposed between the positive electrode active material particles and the second layer.
[0021] According to the manufacturing method described in "8." above, the composite particles described in "2." above can be manufactured.
[0022] 9. In the method for producing a composite particle described in the above "7.", the coating film may be formed to include a second laminated portion. In the second laminated portion, the second layer is interposed between the positive electrode active material particles and the first layer.
[0023] According to the manufacturing method described in "9." above, the composite particles described in "3." above can be manufactured.
[0024] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. [Diagram 2] FIG. 2 is a conceptual diagram showing the second laminated structure. [Diagram 3] FIG. 3 is a conceptual diagram showing the third laminated structure. [Figure 4] FIG. 4 is a conceptual diagram showing the fourth stacked structure. [Diagram 5] FIG. 5 is a conceptual diagram showing an all-solid-state battery in this embodiment. [Figure 6] FIG. 6 is a schematic flow chart of the method for producing composite particles in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] <Terms and definitions, etc.> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0027] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0028] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."
[0029] Unless otherwise specified, the order of execution of the steps, operations, and the like included in various methods is not limited to the order described. For example, the steps may proceed simultaneously. For example, the steps may be performed in sequence.
[0030] For example, a numerical range such as "m to n%" includes the upper limit and the lower limit unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". Furthermore, "m% or more and n% or less" includes "more than m% and less than n%". Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0031] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measurements may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.
[0032] Geometric terms (e.g., "parallel," "perpendicular," "orthogonal," etc.) should not be interpreted in a strict sense. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, etc. in design, work, manufacturing, etc. The dimensional relationships in each drawing may not match the actual dimensional relationships. In order to facilitate understanding of the disclosed technology, the dimensional relationships (length, width, thickness, etc.) in each drawing may be changed. Furthermore, some configurations may be omitted.
[0033] "Upper layer" and "lower layer" refer to the relative positional relationship between two layers in the coating film. The upper layer refers to the layer farther from the positive electrode active material particles, and the lower layer refers to the layer closer to the positive electrode active material particles.
[0034] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.
[0035] "D50" refers to the particle size at which the cumulative frequency from the smaller particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method.
[0036] <XPS / Coverage measurement> The coverage is measured by the following procedure: An XPS device is prepared. For example, an XPS device manufactured by ULVAC-PHI, Inc., product name: PHI X-tool (or equivalent) may be used. A sample powder consisting of composite particles is set in the XPS. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, an analysis software manufactured by ULVAC-PHI, Inc., product name: MulTiPak (or equivalent) may be used. The measurement data is analyzed to obtain C1s, O1s, P2p, B1s, M2p (or M2p 3 / 2 The ratio of each element (element concentration) is calculated from each peak area such as . The coverage rate is calculated using the following formula (1). θ = (P + B) / (P + B + M) × 100 … (1) In the above formula (1), θ represents the coverage (%), and P (phosphorus), B (boron), and M represent the ratio of each element.
[0037] M2p, M2p 3 / 2 In the above formula (1), "M" is a constituent element of the positive electrode active material particles and represents an element other than Li and oxygen (O). That is, the positive electrode active material particles may be represented by the following formula (2). LiMO2…(2) M may be composed of one element or multiple elements. M may include at least one element selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al). When M includes multiple elements, the sum of the composition ratios of the elements may be 1.
[0038] For example, the positive electrode active material particles are "LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2”, the above formula (1) can be transformed into the following formula (1′): θ=(P+B) / (P+B+Ni+Co+Mn)×100…(1') Ni in the above formula (1') is Ni2p 3 / 2 The nickel element ratio is calculated from the peak area of Co2p 3 / 2 The element ratio of cobalt is calculated from the peak area of Mn2p 3 / 2 The element ratio of manganese determined from the peak area is shown.
[0039] <Film thickness measurement> The film thickness (thickness of the coating film) can be measured by the following procedure. A sample is prepared by embedding composite particles in a resin material. A cross-section is processed on the sample by an ion milling device. For example, an ion milling device "Product name Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by an SEM (Scanning Electron Microscope). For example, an SEM device "Product name SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The film thickness is measured in 20 fields of view for each of 10 composite particles. The arithmetic average of the film thicknesses at a total of 200 points is regarded as the film thickness.
[0040] <Composite particles> FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. The composite particle 100 may be referred to as, for example, a "coated positive electrode active material". The composite particle 100 includes positive electrode active material particles 110 and a coating film 120. The composite particle 100 may form, for example, an aggregate. That is, one composite particle 100 may include two or more positive electrode active material particles 110. The composite particle 100 may have, for example, a D50 of 1 to 50 μm, a D50 of 1 to 20 μm, or a D50 of 5 to 15 μm.
[0041] <Coating film> The coating film 120 is a shell of the composite particle 100. The coating film 120 covers at least a part of the surface of the positive electrode active material particle 110. The coating film 120 includes a first layer 121 and a second layer 122.
[0042] <Laminated structure> For example, the coating film 120 may include a first layer 121 and a second layer 122, each of which is independent of each other. For example, the coating film 120 may include a plurality of first layers 121 and a plurality of second layers 122. For example, the first layers 121 and the second layers 122 may be alternately laminated. The total number of the first layers 121 and the second layers 122 may be, for example, 2 to 10 layers, or 2 to 4 layers.
[0043] As long as the coating film 120 includes the first layer 121 and the second layer 122, the coating film 120 may further include additional layers. The coating film 120 may further include, for example, a third layer and a fourth layer (not shown). The third layer and the fourth layer may have a different composition from the first layer 121 and the second layer 122.
[0044] The first layer 121 and the second layer 122 may be stacked in any order. The coating film 120 may include, for example, a first stacked structure (first stacked portion) (see FIG. 1). In the first stacked structure, the first layer 121 is interposed between the positive electrode active material particles 110 and the second layer 122. That is, the first layer 121 is a lower layer, and the second layer 122 is an upper layer.
[0045] The coating film 120 may include, for example, a second laminated structure (second laminated portion). Fig. 2 is a conceptual diagram showing the second laminated structure. In the second laminated structure, the second layer 122 is interposed between the positive electrode active material particles 110 and the first layer 121. That is, the second layer 122 is a lower layer, and the first layer 121 is an upper layer.
[0046] The first layer 121 and the second layer 122 may overlap entirely or partially. For example, the coating film 120 may partially include a single layer structure. FIG. 3 is a conceptual diagram showing a third laminated structure. In FIG. 3, as an example, the lower layer is the first layer 121 and the upper layer is the second layer 122. Of course, the lower layer may be the second layer 122 and the upper layer may be the first layer 121. For example, the coverage of the lower layer may be lower than the coverage of the upper layer. For example, a part of the upper layer may be in contact with the surface of the positive electrode active material particle 110.
[0047] 4 is a conceptual diagram showing the fourth laminated structure. For example, the coverage of the lower layer may be higher than the coverage of the upper layer. For example, a part of the lower layer may be exposed on the surface of the coating film 120.
[0048] <1st layer> The first layer 121 includes a phosphorus compound. The phosphorus compound refers to a compound containing at least P. The first layer 121 may include, for example, a phosphate compound. The first layer 121 may include, for example, a phosphate skeleton. The presence of the phosphate skeleton can be confirmed by TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry). When the first layer 121 includes a phosphate skeleton, in the TOF-SIMS of the composite particle 100, PO2 - , PO3 - Fragments such as:
[0049] The first layer 121 may further contain Li. The phosphorus compound may be represented by, for example, the following formula (3). Li y1 POx1 …(3) In the above formula (3), y1 and x1 are any numbers. y1 and x1 can be identified, for example, by XPS or the like. y1 may, for example, satisfy the relationship 0≦y1<2.5. When y1 is less than 2.5, a reduction in initial resistance is expected. y1 may, for example, be 1.5 or less, 1 or less, 0.5 or less, or zero.
[0050] <Second layer> The second layer 122 includes a boron compound. The boron compound refers to a compound containing at least B. The second layer 122 may include, for example, a boric acid compound. The second layer 122 may include, for example, a boric acid skeleton. The presence of the boric acid skeleton can be confirmed by TOF-SIMS. When the second layer 122 includes a boric acid skeleton, in the TOF-SIMS of the composite particle 100, BO2 - or BO3 - Fragments such as:
[0051] The second layer 122 may further contain Li. The boron compound may be represented by, for example, the following formula (4). Li y2 BO x2 …(4) In the above formula (4), y2 and x2 are any numbers. y2 and x2 can be identified, for example, by XPS or the like. y2 may, for example, satisfy the relationship 0≦y2<2.5. By making y2 less than 2.5, a reduction in initial resistance is expected. y2 may, for example, be 1.5 or less, 1 or less, 0.5 or less, or zero.
[0052] <Film Thickness> The coating film 120 (entire film) may have a thickness of, for example, 5 to 100 nm, may have a thickness of 5 to 50 nm, may have a thickness of 10 to 30 nm, or may have a thickness of 20 to 30 nm.
[0053] The thickness (t1) of the first layer 121 and the thickness (t2) of the second layer 122 may, for example, satisfy the relationship of "t1 / t2=1 / 9 to 9 / 1", or may satisfy the relationship of "t1 / t2=3 / 7 to 7 / 3", or may satisfy the relationship of "t1 / t2=4 / 6 to 6 / 4".
[0054] <Coverage rate> The coverage may be, for example, 95% or more. With a coverage of 95% or more, a reduction in initial resistance is expected. The coverage may be, for example, 95 to 100%, or 96 to 100%.
[0055] 《Cathode active material particles》 The positive electrode active material particle 110 is a core of the composite particle 100. The positive electrode active material particle 110 may be a secondary particle (aggregation of primary particles). The positive electrode active material particle 110 (secondary particle) may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 5 to 15 μm. The primary particle may have a maximum Feret diameter of, for example, 0.1 to 3 μm.
[0056] The positive electrode active material particles 110 may contain any component. The positive electrode active material particles 110 may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 Li(NiCoAl)O2 may contain, for example, LiNi 0.8 Co 0.15 Al 0.05It may contain O2 etc.
[0057] <All-solid-state battery> FIG. 5 is a conceptual diagram showing an all-solid-state battery in this embodiment. The all-solid-state battery 200 includes a power generating element 250. The all-solid-state battery 200 may include, for example, an exterior body (not shown). The exterior body may be, for example, a pouch made of a metal foil laminate film. The exterior body may house the power generating element 250. The power generating element 250 includes a positive electrode 210, a separator layer 230, and a negative electrode 220. That is, the all-solid-state battery 200 includes the positive electrode 210, the separator layer 230, and the negative electrode 220.
[0058] 《Positive electrode》 The positive electrode 210 is layered. The positive electrode 210 may include, for example, a positive electrode active material layer and a positive electrode current collector. For example, the positive electrode active material layer may be formed by applying a positive electrode mixture to the surface of the positive electrode current collector. The positive electrode current collector may include, for example, an Al foil or the like. The positive electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0059] The positive electrode active material layer may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer is in close contact with the separator layer 230. The positive electrode active material layer includes a positive electrode mixture. The positive electrode mixture includes composite particles and a sulfide solid electrolyte. That is, the positive electrode 210 includes composite particles and a sulfide solid electrolyte. Details of the composite particles are as described above.
[0060] The sulfide solid electrolyte can form an ion conduction path in the positive electrode active material layer. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, relative to 100 parts by volume of the composite particles (positive electrode active material). The sulfide solid electrolyte contains sulfur (S). The sulfide solid electrolyte may contain, for example, Li, P, and S. The sulfide solid electrolyte may further contain, for example, oxygen (O), silicon (Si), or the like. The sulfide solid electrolyte may further contain, for example, a halogen, or the like. The sulfide solid electrolyte may further contain, for example, iodine (I), bromine (Br), or the like. The sulfide solid electrolyte may be, for example, a glass ceramic type or an argyrodite type. The sulfide solid electrolyte may include, for example, at least one selected from the group consisting of LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4.
[0061] For example, "LiI-LiBr-Li3PS4" refers to a sulfide solid electrolyte produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio. For example, the sulfide solid electrolyte may be produced by a mechanochemical method. "Li2S-P2S5" includes Li3PS4. Li3PS4 can be produced, for example, by mixing Li2S and P2S5 in a molar ratio of Li2S / P2S5=75 / 25.
[0062] The positive electrode active material layer may further include, for example, a conductive material. The conductive material may form an electronic conduction path in the positive electrode active material layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of carbon black, vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake.
[0063] The positive electrode active material layer may further include, for example, a binder. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The binder may include any component. The binder may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), styrene butadiene rubber (SBR), and polytetrafluoroethylene (PTFE).
[0064] 《Negative electrode》 The negative electrode 220 is layered. The negative electrode 220 may include, for example, a negative electrode active material layer and a negative electrode current collector. For example, the negative electrode active material layer may be formed by applying a negative electrode mixture to the surface of the negative electrode current collector. The negative electrode current collector may include, for example, copper (Cu) foil, Ni foil, or the like. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0065] The negative electrode active material layer may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer is in close contact with the separator layer 230. The negative electrode active material layer includes a negative electrode mixture. The negative electrode mixture includes negative electrode active material particles and a sulfide solid electrolyte. The negative electrode mixture may further include a conductive material and a binder. The sulfide solid electrolyte may be the same or different between the negative electrode mixture and the positive electrode mixture. The negative electrode active material particles may include any component. The negative electrode active material particles may include, for example, graphite, Si, SiO x (0 <x<2)、およびLi4Ti5O 12 may contain at least one selected from the group consisting of:
[0066] <Separator layer> The separator layer 230 is interposed between the positive electrode 210 and the negative electrode 220. The separator layer 230 separates the positive electrode 210 from the negative electrode 220. The separator layer 230 includes a sulfide solid electrolyte. The separator layer 230 may further include a binder. The sulfide solid electrolyte may be the same or different between the separator layer 230 and the positive electrode composite. The sulfide solid electrolyte may be the same or different between the separator layer 230 and the negative electrode composite.
[0067] <Method of manufacturing composite particles> 6 is a schematic flow chart of the method for producing composite particles in this embodiment. Hereinafter, the "method for producing composite particles in this embodiment" may be abbreviated as "this production method". This production method includes "(a) preparation of positive electrode active material particles" and "(b) formation of a coating film". This production method may further include, for example, "(c) heat treatment" or the like.
[0068] (a) Preparation of Positive Electrode Active Material Particles The present manufacturing method includes preparing positive electrode active material particles, the details of which are as described above.
[0069] (b) Formation of coating film This manufacturing method includes manufacturing composite particles by forming a coating film on the surface of positive electrode active material particles. This manufacturing method includes "(b1) Formation of a first layer" and "(b2) Formation of a second layer". Here, as an example, a method of forming a first stacked structure (see FIG. 1) is described. For example, the order of "(b1) Formation of a first layer" and "(b2) Formation of a second layer" may be reversed to form a second stacked structure (see FIG. 2).
[0070] (b1) Formation of the first layer The method includes forming a first layer by drying a first coating liquid. A first coating liquid is prepared. The first coating liquid includes a first solute and a first solvent. The first solute includes a raw material for the first layer.
[0071] The amount of the solute may be, for example, 0.1 to 20 parts by mass, 1 to 15 parts by mass, or 5 to 10 parts by mass, relative to 100 parts by mass of the solvent. The first solvent may contain any component as long as the first solute can be dissolved in it. The first solvent may contain, for example, water, alcohol, etc. The first solvent may contain, for example, ion-exchanged water, ethanol, etc.
[0072] The first solute may include, for example, a phosphoric acid compound. The first solute may include, for example, phosphoric anhydride (P2O5), orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid [(HPO3) n ] and polyphosphoric acid. The first solute may contain at least one selected from the group consisting of, for example, metaphosphoric acid and polyphosphoric acid. Metaphosphoric acid and polyphosphoric acid may have a longer molecular chain than other phosphate compounds. It is considered that the phosphate compound has a long molecular chain, which makes it easier to generate a film (first layer) having continuity. The first layer having continuity is expected to, for example, improve the coverage rate.
[0073] The first solute may further include, for example, a lithium compound. The first solute may include, for example, lithium hydroxide, lithium carbonate, lithium nitrate, etc.
[0074] The first mixture may be formed by mixing the first coating liquid with the positive electrode active material particles. The first mixture may be, for example, a suspension or a wet powder. For example, the suspension may be formed by dispersing the positive electrode active material particles (powder) in the first coating liquid. For example, the wet powder may be formed by spraying the first coating liquid into the powder. In this manufacturing method, any mixing device, granulating device, etc. may be used.
[0075] For example, the first layer can be formed by drying the first mixture. That is, the first coating liquid attached to the surface of the positive electrode active material particles can be dried to generate the first layer. In this manufacturing method, any drying method can be used.
[0076] For example, the first coating liquid may be dried by a spray drying method. That is, the suspension is sprayed from a nozzle to form droplets. The droplets contain the positive electrode active material particles and the first coating liquid. For example, the droplets may be dried by hot air to form the first composite particles (intermediate product).
[0077] The solid content of the suspension for spray drying may be, for example, 1 to 50% or 10 to 30% by volume. The nozzle diameter may be, for example, 0.1 to 10 mm or 0.1 to 1 mm. The hot air temperature may be, for example, 100 to 200°C.
[0078] For example, the first mixture may be formed and the first coating liquid may be dried in a tumbling fluidized bed coating apparatus.
[0079] (b2) Formation of the second layer The method includes forming a second layer by drying a second coating liquid. A second coating liquid is prepared. The second coating liquid includes a second solute and a second solvent. The second solute includes a raw material for the second layer.
[0080] The amount of the solute may be, for example, 0.1 to 20 parts by mass, 1 to 10 parts by mass, or 1 to 5 parts by mass, relative to 100 parts by mass of the solvent. The second solvent may contain any component as long as the second solute can be dissolved in it. The second solvent may contain, for example, water, alcohol, etc. The second solvent may contain, for example, ion-exchanged water, ethanol, etc.
[0081] The second solute may include, for example, a boric acid compound. The second solute may include, for example, at least one selected from the group consisting of orthoboric acid, metaboric acid, and tetraboric acid.
[0082] The second solute may further include, for example, a lithium compound. The second solute may include, for example, lithium hydroxide, lithium carbonate, lithium nitrate, etc.
[0083] The second coating liquid and the first composite particle (intermediate product) may be mixed to form a second mixture. The second mixture may be dried to form a second layer. That is, the second coating liquid attached to the surface of the first composite particle may be dried to generate a second layer. The second composite particle (final product) may be manufactured by generating the second layer. The second composite particle corresponds to the composite particle 100 in FIG. 1. The second coating liquid may be dried, for example, by a spray-drying method, in the same manner as the first coating liquid.
[0084] (c) Heat Treatment The present manufacturing method may include subjecting the first composite particle (intermediate product) and the second composite particle (final product) to a heat treatment. The coating film (each layer) may be fixed by the heat treatment. The heat treatment may also be called "firing". In the present manufacturing method, any heat treatment device may be used. The heat treatment temperature may be, for example, 150 to 300°C. The heat treatment time may be, for example, 1 to 10 hours. For example, the heat treatment may be performed in air, or in an inert atmosphere. The heat treatment may be performed on the first composite particle or the second composite particle, or on the first composite particle and the second composite particle. EXAMPLES
[0085] <Sample preparation> Composite particles, positive electrodes, and all-solid-state batteries according to Nos. 1 to 6 were manufactured as follows. Hereinafter, for example, "composite particles according to No. 1" may be abbreviated as "No. 1".
[0086] No.1 In No. 1, the positive electrode active material particles were subjected to a single coating treatment.
[0087] A first coating liquid (phosphoric acid solution) was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water.
[0088] Positive electrode active material particles: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 was prepared. A suspension was prepared by dispersing 50 parts by mass of the positive electrode active material particles in 53.7 parts by mass of the first coating liquid. A spray dryer manufactured by BUCHI, product name Mini Spray Dryer B-290 (hereinafter the same), was prepared. The suspension was supplied to the spray dryer to produce a powder of composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min. The composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. The coating film (first layer) of No. 1 was made of a phosphorus compound (PO x1 ) (see formula (3) above).
[0089] The following materials were prepared: Sulfide solid electrolyte: 10LiI-15LiBr-75Li3PS4 Conductive material: VGCF Binder: SBR Dispersion medium: heptane Positive electrode collector: Aluminum foil
[0090] A positive electrode slurry was prepared by mixing the composite particles, the sulfide solid electrolyte, the conductive material, the binder, and the dispersion medium. The mixing ratio of the composite particles and the sulfide solid electrolyte was "composite particles / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amount of the conductive material was 3 parts by mass for 100 parts by mass of the composite particles. The amount of the binder was 3 parts by mass for 100 parts by mass of the composite particles. The positive electrode slurry was thoroughly stirred by an ultrasonic homogenizer. The positive electrode slurry was applied to the surface of the positive electrode current collector to form a coating film. The coating film was dried at 100 °C for 30 minutes by a hot plate. In this way, a positive electrode raw sheet was manufactured. A disk-shaped positive electrode was cut out from the positive electrode raw sheet. The area of the positive electrode was 1 cm2. 2 It was.
[0091] A negative electrode and a separator layer were prepared. The negative electrode active material particles were graphite. The same type of sulfide solid electrolyte was used between the positive electrode, the separator layer, and the negative electrode. The positive electrode, the separator layer, and the negative electrode were stacked in a cylindrical jig to form a laminate. The laminate was pressed to form a power generating element. A terminal was connected to the power generating element to form an all-solid-state battery.
[0092] No.2 In No. 2, the positive electrode active material particles were subjected to a single coating treatment.
[0093] A second coating liquid (boric acid solution) was prepared by dissolving 6.7 parts by mass of boric acid (manufactured by Nacalai Tesque, Inc.) in 166 parts by mass of ion-exchanged water. Composite particles, a positive electrode, and an all-solid-state battery were manufactured in the same manner as in No. 1, except that the second coating liquid was used instead of the first coating liquid (phosphoric acid solution). The coating film (second layer) of No. 2 was made of a boron compound (BO x2 ) (see formula (4) above).
[0094] No.3 In No. 3, the positive electrode active material particles were subjected to two coating treatments using one type of coating liquid.
[0095] Positive electrode active material particles: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 was prepared. A suspension was prepared by dispersing 50 parts by mass of a powder of positive electrode active material particles in 26.9 parts by mass of a first coating liquid (phosphoric acid solution). The suspension was supplied to a spray dryer to produce a powder of first composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min.
[0096] A suspension was prepared by dispersing 50 parts by mass of the powder of the first composite particle in 26.9 parts by mass of the first coating liquid (phosphoric acid solution). The suspension was supplied to a spray dryer to produce a powder of the second composite particle. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min. The second composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. After this, the positive electrode and the all-solid-state battery were fabricated in the same manner as No.1.
[0097] No.4 In No. 4, the positive electrode active material particles were subjected to two coating treatments using one type of coating liquid.
[0098] Second composite particles, a positive electrode, and an all-solid-state battery were manufactured in the same manner as in No. 3, except that the second coating liquid (boric acid solution) was used instead of the first coating liquid (phosphoric acid solution).
[0099] No.5 In No. 5, the positive electrode active material particles were subjected to two coating treatments using two different coating solutions.
[0100] Positive electrode active material particles: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 was prepared. 50 parts by mass of the powder of the positive electrode active material particles was dispersed in 26.9 parts by mass of the second coating liquid (boric acid solution) to prepare a suspension. The suspension was supplied to a spray dryer to produce a powder of the first composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min.
[0101] A suspension was prepared by dispersing 50 parts by mass of the powder of the first composite particle in 26.9 parts by mass of the first coating liquid (phosphoric acid solution). The suspension was supplied to a spray dryer to produce a powder of the second composite particle. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min. The second composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. After this, the positive electrode and the all-solid-state battery were fabricated in the same manner as No.1.
[0102] No.6 In No. 6, the positive electrode active material particles were coated twice with two types of coating liquid. No. 6 differs from No. 5 in the order in which the coating liquids were used.
[0103] Positive electrode active material particles: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 was prepared. A suspension was prepared by dispersing 50 parts by mass of a powder of positive electrode active material particles in 26.9 parts by mass of a first coating liquid (phosphoric acid solution). The suspension was supplied to a spray dryer to produce a powder of first composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min.
[0104] A suspension was prepared by dispersing 50 parts by mass of the powder of the first composite particles in 26.9 parts by mass of the second coating liquid (boric acid solution). The suspension was supplied to a spray dryer to produce a powder of the second composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min. The second composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. After this, the positive electrode and the all-solid-state battery were fabricated in the same manner as No.1.
[0105] <Evaluation> The initial resistance of the solid-state battery was measured. The measurement results are shown in Table 1 below. The initial resistance in Table 1 below is a relative value. The initial resistance value of No. 5 is the reference (1.0). The initial resistances of the other samples are expressed as a ratio to the reference.
[0106] [Table 1]
[0107] <Result> Although there is a difference in coverage between the phosphorus compound and the boron compound, the initial resistance is approximately the same (Nos. 1 and 2).
[0108] By coating twice with the same coating solution, the coverage rate tends to increase slightly. However, the initial resistance remains almost unchanged (No. 3, 4).
[0109] By performing two coating processes using two different types of coating liquid, the coverage rate improved significantly and the initial resistance tended to decrease (No. 5, 6). It is believed that some kind of interaction between the first layer (phosphorus compound) and the second layer (boron compound) produced a synergistic effect.
[0110] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]
[0111] 100 composite particle, 110 positive electrode active material particle, 120 coating film, 121 first layer, 122 second layer, 200 all-solid-state battery, 210 positive electrode, 220 negative electrode, 230 separator layer, 250 power generating element.
Claims
1. Positive electrode active material particles; A coating film; Including, the coating film covers at least a part of the surface of the positive electrode active material particle, The coating film includes a first layer and a second layer, the first layer includes a phosphorus compound; the second layer includes a boron compound; The coating film includes a second laminated portion, In the second laminated portion, the second layer is interposed between the positive electrode active material particles and the first layer. composite particles.
2. A coverage rate of 95% or more; The coverage is measured by X-ray photoelectron spectroscopy. The composite particle according to claim 1 .
3. The composite particle according to claim 1 or 2 and a sulfide solid electrolyte are included. Positive electrode.
4. The positive electrode according to claim 3, All-solid-state battery.
5. (a) providing positive electrode active material particles; and (b) forming a coating film on the surface of the positive electrode active material particles to produce composite particles; Including, The (b) is (b1) forming a first layer by drying the first coating liquid; and (b2) forming a second layer by drying the second coating liquid; Including, the first layer includes a phosphorus compound; The second layer includes a boron compound. A method for producing composite particles.
6. The coating film is formed to include a first laminated portion, In the first laminated portion, the first layer is interposed between the positive electrode active material particles and the second layer. The method for producing composite particles according to claim 5 .
7. The coating film is formed to include a second laminated portion, In the second laminated portion, the second layer is interposed between the positive electrode active material particles and the first layer. The method for producing composite particles according to claim 5 .
Citation Information
Patent Citations
All-solid battery
JP2010135090A
Method for manufacturing positive electrode composite material for sulfide all-solid battery
JP2016081822A